Impact of socio-demographic structure of the deaf people communities in prevalence of hereditary hearing loss - O. L. Posukh; M. S. Bady-Khoo; M. V. Zytsar; V. Yu. Mikhalskaia; S. A. Lashin; N. A. Barashkov; G. P. Romanov (Вавиловский журнал генетики и селекции)
Hearing loss caused by environmental or genetic factors concerns more than 10 % of the world population. It leads to disability and considerably reduces the life quality of deaf people. On average, 1 in 1,000 newborns are born deaf, and 50-60 % of cases are due to genetic causes. Nonsyndromic hereditary deafness is a monogenic disease with uniquely high genetic heterogeneity. The prevalence of some forms of genetic deafness varies in different populations and could be determined, as for many other genetic diseases, by the ethnic composition of a population, isolation, founder and «bottleneck» effects, the proportion of consanguineous marriages, and probable heterozygote advantage. It is assumed that high prevalence of hearing loss due to mutations in the GJB2 (Cx26) gene was also influenced by some social factors: a long-standing tradition of assortative marriages between deaf people, combined with growth of their social adaptation and genetic fitness. The start for these events was the breakdown of the deep social isolation of deaf people, which occurred about 300 years ago in Europe, and later in the US, when special schools for the deaf with learning sign language as a common tool for communication were established (linguistic homogamy). Computer simulations and comparative retrospective study showed that over the past 200 years these social processes can have doubled the frequency of deafness in the US caused by the GJB2 gene mutations. Information about the sociodemographic structure of deaf communities in the past is extremely limited by an almost complete lack of relevant archival data. Nevertheless, studies of sociodemographic and medical-genetic characteristics of deaf people’s contemporary communities are important for predicting the prevalence of inherited forms of deafness, as well as for understanding the impact of social factors on the evolutionary processes occurring in human populations.